Stage Directing in Nigeria: A Comparative Study of AbdulRasheed Abiodun Adeoye and Segun Adefila - Tosin-Joshua , Oluwafemi; Julius-Adeoye , Rantimi Jays (Corpus Intellectual, 2025)
Many scholars of theatre directing have credited the Duke of Saxe-Meiningen – the theatre manager as the first acknowledged Western theatre director. The position is based on the history of theatre performances as found in many Western literatures on the subject, even when there are visible evidences to the contrary in other materials. As there were civilizations earlier than that of Greece, invariably, there existed forms of theatrical performance which included directors or managers as well. In many of the ancient religious and ritual performances there were theatrical performances and the priests, priest-kings and or chiefs gave direction for the performances. Therefore, one can argue that priests were among the earliest of theatre directors. Religious priests and troupe leaders of the Yoruba travelling theatre or egungun and strolling players have been known to command and direct the performances of their actors. Non-western theatre directorial techniques have been known to inspire many Western directors like Bertolt Brecht, Antonin Artaud, Jacques Copeau and Peter Brook. This paper looks at the development of different directing technique on Nigeria stage and influences with theatre directors by emphasising the directorial styles of AbdulRasheed Adeoye and Segun Adefila. These two stage directors were purposively selected based on their work with youthful and amateur actors and consistency in play productions. The paper adopts a qualitative research method with descriptive approach to the study of the selected directors by relying on existing literature, performance observation and interview of the subjects.